The Relationship Between Hope And Grit Among Final-Year Students At Malikussaleh University - siahaan, sri kesuma wardhani; Musni, Riza; Anastasya, Yara Andita (Islamic Psychology Study Program, Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
This study aims to examine the relationship between hope and grit among final-year students at Malikussaleh University. The research method used is a quantitative correlational design with an accidental sampling technique. The research respondents consisted of 321 final-year students from the 2018–2020 cohorts who were working on their undergraduate thesis and participated in the study. Data were collected using a hope scale (13 items) and a grit scale (12 items), both modified by the researcher. Hypothesis testing was conducted using nonparametric statistics with Spearman’s rho correlation. The results indicate a very strong and significant positive relationship between hope and grit among final-year students at Malikussaleh University (r = 0.815, p =0.000). This finding suggests that higher levels of hope are associated with higher levels of grit, while lower levels of hope correspond to lower levels of grit in this population. The highest correlation within the hope construct was found in the agency thinking dimension, whereas the highest correlation within the grit construct was observed in the perseverance of effort dimension.